Foliar feeding of NPK as partial substitution of soil applied fertilizers for improving corn growth and decrease pollution - Abou El-Nour, E. A. A.; Abdel-Maguid, A.A. (2003)
Two experiments were carried out during the summer season of 2002 on corn. One of them was carried out at the green house of "Micronutrients Project" National Research Centre and the other at the Agricultural Research Station of National Research Centre, Kalubia Governorate. The objective was to through some light on foliar feeding of NPK as a partial substitution of conventional NPK practices. Treatments were the recommended rate of soil NPK (control) in addition to four treatments' 3/4; 1/2, 1/4 soil NPK recommended combined with three foliar sprays with NPK compound (19: 19: 19) at rate of 2.5 g/liter and three foliar sprays with the aforementioned compound without any NPK soil addition
Includes references.
Summary in Arabic.
1
Keywords: Corn -- Growth; Corn -- Fertilizers; Foliar feeding; Nitrogen fertilizers